Tuberkulóza v Ceské republice v roce 2009 - Homolka, Jirí; Krejbich, Frantisek; Holub, Jirí (Casopis lekaru ceskych, 2011)
BACKGROUND: The number of notified tuberculosis cases in the Czech Republic in 2009 was lower than in 2008. 710 new tuberculosis cases and relapses were reported. MATERIAL AND METHODS: 598 cases were pulmonary tuberculosis and from them 439 were proved pulmonary tuberculosis cases. In 2009 235 smear-positive cases of pulmonary tuberculosis were diagnosed. RESULTS: The incidence of tuberculosis was 6.8/100000 inhabitants in 2009. The percentage of tuberculosis cases diagnosed in foreign-born persons living in the Czech Republic increased from 14.2% in 2003 to 19.2% in 2009. CONCLUSIONS: Next targets of tuberculosis control in the Czech Republic must be an active case-finding in the high-risk groups and monitoring of latent tuberculosis infection.
Keywords: dítě; lidé středního věku; mladiství; mladý dospělý; Male; dospělí; incidence; tuberkulóza; Incidence; lidé; senioři; Aged; Czech Republic; Tuberculosis; Česká republika; Adolescent; Child, Preschool; ženské pohlaví; Young Adult; Tuberculosis, Pulmonary; Adult; mužské pohlaví; předškolní dítě; plicní tuberkulóza; Child; Middle Aged; Humans; Female